2015
DOI: 10.1111/ajd.12401
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance confocal microscopy is a useful non‐invasive tool in the in vivo diagnosis of pigmented basal cell carcinoma in Asians

Abstract: This case series shows the value of non-invasive in vivo RCM imaging in the differentiation of malignant and benign pigmented lesions. Early diagnosis of small, pigmented BCC allows earlier excision with better prognosis. Future biopsies of benign lesions in cosmetic areas could also be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…RCM is a rapidly developing optical microscope, which exhibits different expressions in different degree of brightness through different refractive indexes of different tissues or cells, thus forming in vivo three‐dimensional imaging, and making it possible to observe cell morphology and arrangement directly 7 . It is in good agreement with histopathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RCM is a rapidly developing optical microscope, which exhibits different expressions in different degree of brightness through different refractive indexes of different tissues or cells, thus forming in vivo three‐dimensional imaging, and making it possible to observe cell morphology and arrangement directly 7 . It is in good agreement with histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…It is in good agreement with histopathology. It has been used to evaluate a variety of skin diseases, including BCC, 7 SK, 8 melanoma, 9 psoriasis, 10 and acne 11 . Gerger et al 12 and Langley et al 13 evaluated the diagnostic ability of RCM in melanoma tumors, verified the applicability of RCM in differential diagnosis of benign nevus and melanoma, and demonstrated that RCM was more sensitive than dermoscope.…”
Section: Discussionmentioning
confidence: 99%
“…While the diagnostic accuracy will vary with assessor capabilities, RCM is a useful tool when it is challenging to examine pigmented lesions with a dermatoscope. RCM is a helpful add-on to dermoscopy to increase the diagnostic sensitivity and aid in the clinical decision making around referring to surgery and it allows clinicians to avoid biopsying lesions unnecessarily ( 74 76 ).…”
Section: Ir-based Imaging Modalitiesmentioning
confidence: 99%
“…Modern optical imaging modalities such as wide-field fluorescence imaging 9 , confocal microscopy 10 , optical coherence tomography (OCT) 1113 , polarization-sensitive OCT 14,15 , OCT-based angiography (OCA) 16,17 and photoacoustic imaging 18 and their combinations 19,20 offer new possibilities for detection and visualization of human skin tumor structure and microvascular network in real time. OCT is particularly promising as it offers non-invasive structural and functional 3D imaging of biological tissues with high spatial resolution 11 , in particular for BCC 9,13,21 .…”
Section: Introductionmentioning
confidence: 99%